2015
DOI: 10.1007/s00262-015-1759-4
|View full text |Cite
|
Sign up to set email alerts
|

Late administration of murine CTLA-4 blockade prolongs CD8-mediated anti-tumor effects following stimulatory cancer immunotherapy

Abstract: We have demonstrated that immunostimulatory therapies such as interleukin-2 (IL-2) and anti-CD40 (αCD40) can be combined to deliver synergistic anti-tumor effects. While this strategy has shown success, efficacy varies depending on a number of factors including tumor type and severe toxicities can be seen. We sought to determine whether blockade of negative regulators such as cytotoxic T lymphocyte antigen-4 (CTLA-4) could simultaneously prolong CD8+ T cell responses and augment T cell anti-tumor effects. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…-Global knockout: lethal autoimmunity 67,68 -Deletion in adult mice: non-lethal autoimmune disease 69 -In vivo blockade: autoimmune disease exacerbation in multiple murine models (diabetes, EAE, etc.) 71,72 -Human disease association: multiple including T1D, autoimmune thyroid disease, and rheumatoid arthritis [267][268][269] -Inducible knockout: No effect on tumor growth 73 -Conditional deletion in Tregs: Reduced transplantable tumor growth 9 -In vivo blockade: Tumor control and/or regression in murine tumor models 66,154,155,224 -First FDA-approved checkpoint blockade therapy for metastatic melanoma 213 PD-1 (programmed death-1) -Global knockout: Severe autoimmune disease. Phenotype depends on mouse strain: BALB/c lethal dilated cardiomyopathy, C57BL/6 mice lupus-like autoimmune disease, NOD mice exacerbated diabetes 81-83 -In vivo blockade: Accelerated and more severe EAE 84 -Human disease association: Multiple including SLE, T1D, ankylosing spondylitis, and rheumatoid arthritis [85][86][87][88] -Global knockout, in vivo blockade or conditional deletion of PD-1 in T cells lead to accelerated tumor clearance in multiple murine cancer models [168][169][170][171] Co-inhibitory receptors on T cells in anti-tumor immunity: a focus on CTLA-4, PD-1, TIM-3, TIGIT and LAG-3 Promptly after their discovery, investigations aiming to target coinhibitory receptors arose and established a new paradigm in therapies for cancer.…”
Section: T-cell Exhaustion In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…-Global knockout: lethal autoimmunity 67,68 -Deletion in adult mice: non-lethal autoimmune disease 69 -In vivo blockade: autoimmune disease exacerbation in multiple murine models (diabetes, EAE, etc.) 71,72 -Human disease association: multiple including T1D, autoimmune thyroid disease, and rheumatoid arthritis [267][268][269] -Inducible knockout: No effect on tumor growth 73 -Conditional deletion in Tregs: Reduced transplantable tumor growth 9 -In vivo blockade: Tumor control and/or regression in murine tumor models 66,154,155,224 -First FDA-approved checkpoint blockade therapy for metastatic melanoma 213 PD-1 (programmed death-1) -Global knockout: Severe autoimmune disease. Phenotype depends on mouse strain: BALB/c lethal dilated cardiomyopathy, C57BL/6 mice lupus-like autoimmune disease, NOD mice exacerbated diabetes 81-83 -In vivo blockade: Accelerated and more severe EAE 84 -Human disease association: Multiple including SLE, T1D, ankylosing spondylitis, and rheumatoid arthritis [85][86][87][88] -Global knockout, in vivo blockade or conditional deletion of PD-1 in T cells lead to accelerated tumor clearance in multiple murine cancer models [168][169][170][171] Co-inhibitory receptors on T cells in anti-tumor immunity: a focus on CTLA-4, PD-1, TIM-3, TIGIT and LAG-3 Promptly after their discovery, investigations aiming to target coinhibitory receptors arose and established a new paradigm in therapies for cancer.…”
Section: T-cell Exhaustion In Cancermentioning
confidence: 99%
“…221 Multiple investigations of optimized therapies (combination with other therapies, treatment kinetics, specificity, various Igisotypes or Fc-engineered antibodies) aim to improve the efficacy while mitigating the toxicity of anti-PD1 and anti-CTLA-4 antibodies. [222][223][224] Interestingly, a recent study showed that in combination with vaccines against tumor-associated antigens, the timing of anti-PD-1 blockade influences therapeutic outcome. Particularly, PD-1 blockade under suboptimal priming conditions leads to the emergence of a subset of dysfunctional CD8 + T cells that prevent antitumor immunity.…”
Section: Manipulating T-cell Exhaustion In Cancermentioning
confidence: 99%
“…However, the designs of these types of studies are often empirical and take a straightforward additive approach that may not be optimal considering the unique immunological mechanisms that influence combination treatments. While others have demonstrated that administering checkpoint blockade “late” or for a longer duration than costimulatory antibodies is beneficial with preclinical combination immunotherapies (41,42), to our knowledge ours is the first report to directly compare concurrent combination treatment with non-overlapping, sequential treatment with the same agents. Given that a substantial portion of patients does not respond to PD-1 blockade (in monotherapy or in combination) (1,3), our findings in anti-PD-1 refractory model systems suggest that the use of costimulatory stimulation may impact these patients.…”
Section: Discussionmentioning
confidence: 89%
“…Enhanced antitumor effects of checkpoint blockade and local treatment with CpG have been reported (44, 45). A combinatorial therapy using anti-CTLA-4 and agonistic anti-CD40 induced a stronger T cell-mediated antitumor effect than either treatment given individually (46, 47). Anti-CTLA-4 was synergistic with the immunocytokine L19-IL2 (34).…”
Section: Discussionmentioning
confidence: 99%